The Influence of Managerial Ability on Future Performance - Luqita Romaisyah; Zahroh Naimah (Journal of Economics, Business, and Government Challenges, 2018)
The establishment of a single market in the ASEAN which is termed the ASEAN Economic Community (MEA) allows a country to sell goods and services easily to other countries throughout Southeast Asia, thus competition is getting tighter. Every firm should be more innovative in order to have a competitive advantage to win the competition in the industry which is reflected by its performance. Managers with a high ability are believed to be able to make projections of future business conditions, thus they can design the right strategy for the procurement and optimization of the firm's resources utilization in producing output which can lead the firm to has a good performance in future. This study analyze the influence of managerial ability to future performance. Some control variables are used in this study, including firm size, financial leverage, market to book ratio, sales growth, and market share.Hypothesis testing in this study used multiple linear regression analysis to analyze data from 291 manufacturing companies listed on the Indonesia Stock Exchange during the 2008-2010 period. The result prove that managerial ability has a positive effect on future performance up to five years later, but the longer time the influencebecome weaker.